Giving more detailed information about health insurance encourages consumers to choose compromise options - Chick, Stephen E.; Hawkins, Scott A.; Soberman, David (Frontiers in Psychology, 2023)
This study investigates how the provision of additional information affects the level of coverage that people choose to insure against uncertain future events that entail significant out of pocket costs. The specific context we examine is that of young adults choosing between different levels of healthcare insurance in the context of taking their first full time job. In two locations (Paris, France and Toronto, Canada), university students were recruited for a study in which they imagined they were making choices about the healthcare coverage associated with the taking a new job. Every participant made choices in four categories: Physician Care, Clinical Care, Hospital Care and Dental Care. Participants were randomly assigned to one of two conditions: Low Detail or High Detail coverage information, and they chose between three levels of coverage: Basic, Enhanced and Superior. Our study shows that the provision of more detailed information about the health events and procedures covered by a healthcare plan led to a compromise effect in which participants shifted their choices significantly towards Enhanced (moderate coverage) from Basic (low coverage) and Superior (high coverage). The compromise effect was observed at both locations; however, Paris participants chose significantly higher levels of coverage than did Toronto participants. This implies that providing more detail to employees about the health events and procedures covered by a healthcare plan will increase the fraction of employees who choose the intermediate level of coverage. It is beyond the scope of this study to conclude whether this is good or bad; however, in a context where employees gravitate to either insufficient or excessive coverage, providing additional detail may reduce these tendencies.